Proposta de metodologia para organização e representação de trilhas de aprendizagem no contexto da educação corporativa na administração pública - Patricia Lopes Ferreira (2018)
The learning paths can be understood as a systematic and multimodal set of learning units, containing different navigation schemes, ranging from linear models, prescriptive models, to more hierarchical models, and to network models, whose navigation is freer, and whose purpose is the development of skills. In the field of Corporate Education, these learning paths tend to contribute to a better use of the resources invested in initial and continuing training, in addition to making it possible to overcome the one-size-fits-all approach. From the point of view of Librarianship and Information Science, the learning paths are manifested in a way analogous to hypertext, understood as the grouping of nodes and links arranged in a nonlinear way. Although hypertext has been widely used since the 1990s, there is a lack of consolidated methodologies for the construction of this resource. However, even considering this gap, it is evaluated that studies and applications of this field can be a reference for identification of methods and techniques to be adapted for construction of learning paths. Thus, in this research, we investigate how the principles of construction of hypertext systems can be adopted to improve the organization and representation of learning paths. It was observed that these principles have been used in the construction of the learning paths, however, it is assumed that this use is still intuitive and not systematized, and may make it difficult to apply in different situations. Aiming to contribute to the systematization of these empirical applications, the objective of this study is to elaborate a methodology for organization and representation of learning paths, based on the principles of structuring hypertext systems, in the scope of Corporate Education in public administration. The delimitation of the context is necessary, considering possible differences of application to other segments of education. In order to structure this methodology, the following procedures were used: to demonstrate how the strategies for organization and representation of learning paths identified in the literature review are adherent to the structuring principles of hypertext systems; to identify common elements of strategies of organization and representation of learning paths that have been applied in an empirical or referenced way; and outline a conceptual meta-model of representation of learning paths. The results indicated that the requirements of elaboration of methodologies for conceptual models of hyperdocuments adopted in this research are applicable and useful to the context of creation of methodologies for organization and representation of learning paths. It was also identified that there are empirical experiences about the organization and representation of learning paths in the context of public administration, although some of the identified methodologies have not been systematized. It was also observed that the analysis of interfaces of learning paths can contribute to the creation of a conceptual meta-model of representation of these learning paths, although the need for refinement of this conceptual model was also identified. It is concluded that these results can bring a relevant contribution to the public administration, since it was possible to systematize a conceptual model, as well as phases and stages of a methodology for organization, representation and management of learning paths in the context of Education Corporate. It is understood that the application of the methodology will contribute to optimize the processes of planning, execution and management of Corporate Education in public administration, and may also help optimize public spending in this segment. It is hoped that the proposed methodology may also be useful to fill the gap identified in the literature, which will promote the development of future research related to the subject